Історико-краєзнавча характеристика топонімів с. Лецьки на Переяславщині - Юрченко, О. (Краєзнавство, 2009)
У публікації подається коротка характеристика топонімів с. Лецьки. Розглядаються фактори їх формування в контексті історичного розвитку села. В публикации изложена краткая характеристика топонимов с. Лецки. Рассматриваются факторы их формирования в контексте исторического развития села. The given publication offers a short characteristic of the placenames of the village of Letsky and considers the factors of their formation in the context of the village’s historical development.